2002
DOI: 10.1084/jem.20011963
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of the Same Glycolipid by Different CD1 Molecules

Abstract: Five CD1 molecules are expressed in humans and it is unclear whether they have specialized or redundant functions. We found that sulfatide is a promiscuous CD1-binding ligand and have isolated T cell clones that are specific for sulfatide and restricted by distinct CD1 molecules. These clones have been used to compare the capacity of different CD1 to present the same glycolipid, to induce effector functions, and to form persistent immunogenic complexes. CD1a, CD1b, and CD1c molecules similarly load sulfatide o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
198
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(206 citation statements)
references
References 40 publications
8
198
0
Order By: Relevance
“…We previously reported that both wild-type and soluble mCD1d1 assemble with PI and PI-glycans in vivo (11,12). However, in vitro, CD1 appears to bind a wide variety of lipids that vary in the chemical character of the moiety that directly interacts with the antigen-binding groove (11,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Therefore, our previous findings (11,12) may have been biased by the techniques used for the extraction, purification, and analyses of mCD1d1-associated ligands.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…We previously reported that both wild-type and soluble mCD1d1 assemble with PI and PI-glycans in vivo (11,12). However, in vitro, CD1 appears to bind a wide variety of lipids that vary in the chemical character of the moiety that directly interacts with the antigen-binding groove (11,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Therefore, our previous findings (11,12) may have been biased by the techniques used for the extraction, purification, and analyses of mCD1d1-associated ligands.…”
Section: Resultsmentioning
confidence: 79%
“…These lipids include cellular phospholipids and sphingolipids as well as mycobacterial phospholipids and mycolates (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Remarkably, however, CD1 molecules appear to associate with a restricted variety of lipids in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…CD1 proteins present a variety of pathogen-derived lipids to T cells in vitro (1)(2)(3)(4)(5)(6), and T cells reactive to mycobacterial lipid Ags have been isolated from the bloodstream of tuberculosis patients, providing evidence that CD1 and lipid-reactive T cells normally function in the host response during infections with Mycobacterium tuberculosis (7)(8)(9). However, CD1-mediated T cell responses are not limited only to foreign pathogens, as endogenous mammalian phosphatidylinositols normally bind to cellular CD1 proteins as they traverse the secretory pathway (10,11), and self gangliosides, phosphatidylinositols, sulfatides, and isoglobosides activate CD1-restricted T cells (12)(13)(14)(15)(16). Thus, mammalian APCs normally encounter and present both foreign and self lipid Ags to T cells, raising basic questions about how such responses are regulated.…”
mentioning
confidence: 99%
“…This might reflect intrinsic structural features limiting their antigenicity and/or a difficulty in breaking tolerance to self. Some GSL, such as sulphatide, form stimulatory complexes with all CD1 molecules, thus behaving as promiscuous antigens [1].…”
Section: Structure Of Exogenous and Self-lipid Antigensmentioning
confidence: 99%
“…An intriguing issue is how the route of internalization contributes to lipid antigenicity. Sulphatide, which is internalized by clathrin-coated vesicles, can form complexes with all CD1 molecules [1], suggesting that this type of internalization is permissive for the generation of all types of CD1 complexes. Whether glycolipids that are internalized through caveolae can also form complexes with all CD1 molecules remains unknown.…”
Section: Lipid Traffic Within Cellsmentioning
confidence: 99%